Desiderius Erasmus and Christian Education - Wingga Witsi Lumangkun; Valentino Reykliv Mokalu (JETL (Journal of Education, Teaching and Learning), 2022)
The aims of this article is to discuss the problem of challenges from the perspective of humanism in its correlation with christian religious education. Desiderius Erasmus gave a big contribution to the development of humanism itself, because humans need to self expolarate themselves freely, so that the essence of his view of humanism makes a clear contribution to humans who can actualize themselves to humanize humans. The research method used in this article is library re-search with an interpretive approach where the meaning of the text is raised as the text speaks. In conclusion, Humanism basically teaches humans that all humans are the same there are no differences, which is part of the world and god's creation. The application of the humanism viewpoint in christian religious education can not only help to deal with conflicts based on differences but also can help unite humanity based on human values itself.